Methodological indicators for teaching practice and their relationship with educational practice: Perceptions of completeers of degree courses in biology at higher education institutions in Boa Vista/Roraima/Brazil (Research, Society and Development, 2024)
This study seeks to investigate the methodological indicators for Teaching Practice and its relationships with Educational Practice, given the perceptions of those completing Biology Degree courses at Higher Education Institutions in Boa Vista/Roraima/Brazil. Through analysis of data collection instruments (ICD), answered by them, based on the methodologies used in the classroom. An attempt is made to answer the problem: are the methodological indicators used in teaching practice in Biology Degree courses consistent with educational practice? It adopted qualitative – quantitative foundations and a hermeneutic method, through content analysis and data interpretation. As a sample, there were 72 graduates and 20 teachers from 5 Higher Education Institutions in 2008. Two ICDs and two analytical matrices were used. In the first matrix, graduates who had already concluded, teachers and graduates were interviewed, taking into account the indicators methodologies analyzed in ICD 01; in the second matrix, a relationship was made between the Methodological initiators, relating to the principles of Educational Practice, Teaching and the professional profile. With the undergraduates' conceptions in hand, it can be highlighted that the methodological indicators for Educational Practice represent a significant advance in Higher Education in the State. Because there are qualified and committed teachers in the profession, with conditions both for developing methodologies and for developing research and improving the quality of teaching and learning.